2005
DOI: 10.1590/s0004-27302005000300007
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporose após transplante de órgãos sólidos

Abstract: RESUMOA osteoporose é uma complicação comum após os transplantes de rim, coração, fígado e pulmão. Os esquemas imunossupressores para evitar a rejeição do órgão enxertado após o transplante freqüentemente incluem glicocorticóides, ciclosporina A e tacrolimus, os quais possuem efeitos danosos sobre a homeostase mineral óssea, impostos a um esqueleto já comprometido. Outros fatores que provavelmente contribuem para a patogênese da osteoporose pós-transplante são deficiência de vitamina D, hiperparatireoidismo se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
8
0
2
Order By: Relevance
“…Pre-clinical studies have shown that use of immunosuppressive drugs reduces bone density and also impairs healing of vascularized allografts and dental implant osseointegration (14,15). Also bone metabolism is significantly altered by chronic exposure to glucocorticoids, chronic exposure to glucocorticoids constituted the most common cause of secondary osteoporosis, mainly affecting trabecular bone (16).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have shown that use of immunosuppressive drugs reduces bone density and also impairs healing of vascularized allografts and dental implant osseointegration (14,15). Also bone metabolism is significantly altered by chronic exposure to glucocorticoids, chronic exposure to glucocorticoids constituted the most common cause of secondary osteoporosis, mainly affecting trabecular bone (16).…”
Section: Discussionmentioning
confidence: 99%
“…4 Bone loss would be greater in the first 12 to 18 months of therapy and is directly related to the dose and duration of treatment. 9 Glucocorticoids have great effects on mineral homeostasis, and may stimulate parathyroid hormone (PTH) secretion both in a direct and an indirect manner. 9 Indirect increase results from diminished intestinal calcium absorption and increase in urinary calcium excretion.…”
Section: Literature Review Glucocorticoids (Gc)mentioning
confidence: 99%
“…9 Glucocorticoids have great effects on mineral homeostasis, and may stimulate parathyroid hormone (PTH) secretion both in a direct and an indirect manner. 9 Indirect increase results from diminished intestinal calcium absorption and increase in urinary calcium excretion. In the kidney, there is a reduction in calcium and phosphate tubular absorption.…”
Section: Literature Review Glucocorticoids (Gc)mentioning
confidence: 99%
See 2 more Smart Citations